Gênero como construção social: elementos constituintes para o ensino de ciências - Alboredo, Bruna Dias (Universidade Federal de São Carlos, 2023)
Although gender is defined as a social construction, which reflects social markers, it is necessary to understand in more depth how this construction occurs in different cultures and historical contexts, especially in science education and teaching. In this work, we aim to analyze how research in science teaching has been working gender over time, based on a bibliographical survey, interpreting elements that may contribute to these discussions. For that, we try to present several definitions of gender that configure it as a socially constructed category, in addition to showing the importance of education against barbarism in the anti-gender discourse. The research methodology used was bibliographical research, through the CAPES journal portal, and the data analysis methodology was discursive textual analysis (DTA). According to the data analysis, 4 metatexts were produced. It was possible to conclude that research in science teaching has not been working on the gender issue, because of the little importance given to the theme and the moral panic around this concept.
Gender as a social construction: constituent elements for science teaching
Keywords: Pesquisa bibliográfica; Identidade de gênero; Papéis de gênero; Ciências; Bibliographic research; Gender identity; Gender roles; Science; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO